34 The role of the roald dahl swan (syndromes without a name) clinical nurse specialist; the first 12 months experience. (4th October 2017) - Jewitt, A; Rosser, E; Clement, E; Hurst, J; Taffinder, S; Dziwinski, S
Abstract : Background: Great Ormond Street Hospital (GOSH) looks after many children with complex needs, many of which will have an underlying genetic cause for their condition. In some cases a diagnosis can be made but in others, despite numerous investigations, a diagnosis is not achieved. These patients are collectively described as having 'Syndromes without a Name' (SWAN). There are approximately 6000 patients born in the UK each year with a genetic condition that is as yet undiagnosed. These individuals are frequently under the care of multiple specialities and hospitals, leading to disjointed and complicated multidisciplinary care. The patient and family often struggle to navigate the healthcare system compounded by the lack of information about the underlying condition. Having no diagnosis can make it harder to obtain financial help and educational support. Strategy: In collaboration with Roald Dahl's Marvellous Children's Charity, a pilot study assessed the needs of this patient group. Following this study a Roald Dahl SWAN CNS role was created at GOSH in April 2016, the first post of its kind in the UK. We present a summary of the work undertaken in the first year of this post and show how the role has improved the care of these families at GOSH. Results: In the first year, 40 families were referred to the SWAN CNS. On average patients are aged 4 years at referral and are under 7 different GOSH teams. Families need support from the CNS in many different areas including attendance at appointments to help understand and process clinical information; coordination of appointments to streamline visits to GOSH and the provision of on-going emotional and social support. Conclusion: Feedback from families and clinicians has been universally positive and a formal qualitative assessment of the role is in progress.